Preeclampsia and Future Cardiovascular Risk: Are Women and General Practitioners Aware of This Relationship? The Experience from a Portuguese Centre. (28th May 2014) - Viana Pinto, Pedro; Rei, Mariana; Machado, Ana Paula; Montenegro, Nuno
Abstract : Objective . To evaluate the impact of preeclampsia in the modification of lifestyle habits and decreasing cardiovascular risk factors in a population of women at least 6 months after having the diagnosis of preeclampsia. Methods . Cross-sectional observational study. Data included 141 cases of preeclampsia and chronic hypertension with superimposed preeclampsia on singleton births diagnosed in our institution between January 2010 and December 2013. From the cases diagnosed over 6 months a standardized questionnaire evaluating lifestyle changes was applied. Results . We reviewed 141 cases, of which 120 were diagnosed for more than 6 months. An overall participation rate in the questionnaire of 65% was yielded. A slight increase from the mean BMI before pregnancy was found. No statistical significant association was established between postpregnancy mean BMI, weight variation, and the frequency of aerobic exercise with the severity of preeclampsia. Only 28% of our cases were practising aerobic exercise at least weekly. The majority of women assessed blood pressure at least monthly (45/78), but only 25 assessed glycaemia at least once/year. Conclusion . This study shows that the majority of our patients and general practitioners do not take into consideration a previous pregnancy affected by preeclampsia as a risk factor for future cardiovascular disease.